Analisis Pelaksanaan Tahapan Kampanye dan Sosialisasi pada Pemilihan Bupati dan Wakil Bupati Kabupaten Mandailing Natal Tahun 2020 Dalam Kondisi Bencana Covid-19 - Ardiansyah Hidayat; Heri Kusmanto; Hatta Ridho (PERSPEKTIF, 2022)
The purpose of this study was to describe how the process and the inhibiting factors for the implementation of the socialization and campaign for the 2020 Madina Regency Election during the Covid-19 Pandemic. This qualitative approach is directed at the background and the individual holistically or intact. The use of each research method depends on three things, namely: first, the type of research question; second, the control the researcher has over the behavioral events that he will study, and third the focus on the phenomenon of his research concerning current or historical phenomena. The results of the study stated that the socialization process carried out by the KPU and Bawaslu in Mandailing Natal Regency was a determining part of people's political behavior. The reason is that the implementation of socialization forms values that indicate how elections should take place and each member of the community in Mandailing Natal Regency participates in the political system. In general, implementing the decision to conduct elections during the Covid-19 Pandemic at the Mandailing Natal Pilkada is a challenge in organizing elections, making new and urgent demands on how elections are managed. The Covid-19 pandemic has symbolically thwarted the social rituals of voters with the power of their individual votes being able to determine who should lead them in the results of the 2020 Simultaneous Pilkada.